2020
DOI: 10.1128/jb.00716-19
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Transporter PstSCAB of Campylobacter jejuni Is a Critical Determinant of Lactate-Dependent Growth and Colonization in Chickens

Abstract: Campylobacter jejuni causes acute gastroenteritis worldwide and is transmitted primarily through poultry, in which it is often a commensal member of the intestinal microbiota. Previous transcriptome sequencing (RNA-Seq) experiment showed that transcripts from an operon encoding a high-affinity phosphate transporter (PstSCAB) of C. jejuni were among the most abundant when the bacterium was grown in chickens. Elevated levels of the pstSCAB mRNA were also identified in an RNA-Seq experiment from human infection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…This transporter was predicted as a potential fitness factor in 3 species. It is well known that pst mutants are attenuated in other species [Proteus mirabilis in a biofilm and UTI model (36,48) and Campylobacter jejuni in the murine gut model of infection (49)]. Thus, we attempted to validate this finding for bacteremia by testing pstSCABphoU mutants of all five species in the murine model of bacteremia and found that two, E. coli CFT073 and E. hormaechei UM_CRE_14, were attenuated (Fig…”
Section: Resistance To Complement and Osmotic Stress Enterobacterialmentioning
confidence: 88%
“…This transporter was predicted as a potential fitness factor in 3 species. It is well known that pst mutants are attenuated in other species [Proteus mirabilis in a biofilm and UTI model (36,48) and Campylobacter jejuni in the murine gut model of infection (49)]. Thus, we attempted to validate this finding for bacteremia by testing pstSCABphoU mutants of all five species in the murine model of bacteremia and found that two, E. coli CFT073 and E. hormaechei UM_CRE_14, were attenuated (Fig…”
Section: Resistance To Complement and Osmotic Stress Enterobacterialmentioning
confidence: 88%
“…The C. jejuni lctP :: kan mutant was constructed by inserting a kanamycin resistance cassette into the gene as previously described (51). Briefly, 500 bp of both upstream and downstream regions of the lctP locus was amplified by PCR with primers containing Sma I restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…The strains were restreaked and grown for 16 h. The bacteria were suspended in MH broth and inoculated in 25 ml of MH broth containing the desired antibiotics to an initial optical density at 600 nm (OD 600 ) of approximately 0.05. Bacterial numbers were measured at different times up to 48 h. To determine the growth of C. jejuni , strains were grown in MCLMAN minimal medium containing 0.5% partially purified gastric mucin and various carbon sources, including sodium pyruvate, sodium butyrate and L-lactate (28, 51), as noted. Growth was measured via absorbance at OD 600 up to 48 h after inoculating at an initial OD 600 of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CJ load in different organs was determined by plating the serially diluted samples on Campylobacter selective Mueller-Hinton (MH) agar plates supplemented with 10% sheep's blood, 40 µg/mL cefoperazone, 100 µg/mL cycloheximide, 10 µg/mL trimethoprim and 100 µg/mL vancomycin. Plates were incubated at 37° C for 48 h under microaerobic conditions and the number of colonies was subsequently counted [32]. ST and SE counts were enumerated by plating the serially diluted samples on Xylose Lysine Deoxycholate (XLD) agar plates followed by incubation at 37° C for 24 h and subsequent counting of the colonies in plates.…”
Section: Bacterial Colonization Assessmentmentioning
confidence: 99%